Elastic-Viscoplastic Constitutive Model of Soil under Cyclic Loading - Yuan Ma; Hua Liang; Yongxue You; Weiguang Zhang; Limin Guo; Jianwei Fan; Zhihui Cao (Advances in Civil Engineering, 2021)
The creep problems are often involved in soil under cyclic loading, and its behaviors of soil under cyclic loading sparks many arguments in current research field. To propose one new model to demonstrate these creep behaviors of soil under cyclic loading, the cyclic loading was simplified equivalently, and the elastic-viscoplastic model (EVPM) for soil under cyclic loading was established based on the Bingham model. The yield criterion for soil under cyclic loading with constant amplitude was proposed following the simplified load. A constitutive equation based on the EVPM was constructed by using the flow criterion related to the yield criterion. Meanwhile, the parameters of EVPM were identified and discussed. In addition, the case analysis of the EVPM was also performed. The results indicate that the stable and destructive creep behaviors of soil under cyclic loading could be well described by the recommended EVPM, and the obtained parameters in the model exhibited a clear regularity with the increase of dynamic stress amplitude. Besides, the established model could be selected to predict the stable and destructive creep behavior of soil under cyclic loading.